Analysis Of the Strength of The Structure of The Multi-Story Building of Universitas Pembangunan Panca Budi Using Sliding Walls Using the Pushover Analysis Method - Annisa Adika Qolby (Journal of Information Technology, computer science and Electrical Engineering, 2024)
This study aims to analyze the strength of the structure of the multi-storey building of Panca Budi Development University using a shear wall through the Pushover Analysis method. This analysis is important considering the importance of ensuring the safety needs of the structure for building users. The research method used is numerical analysis with structural modeling using ETABS software v.19.0.0. Primary data is obtained through direct measurement of structural dimensions and material testing in the field, while secondary data is obtained from building planning documents. Pushover analysis is carried out by monotonic static lateral loading which is gradually increased until the structure collapses. The analyzed parameters include the shear capacity of the foundation, lateral displacement and the collapse mechanism of the structure. The results show that the building structure with the addition of sliding walls has a maximum basic shear capacity of 12,450 kN, with a maximum lateral displacement on the roof of 0.235 meters. The performance level of the structure is in the Life Safety (LS) category based on FEMA 356, which indicates that the structure is able to withstand the planned earthquake load well. The addition of sliding walls increases the lateral stiffness of the structure by 45% compared to the structure without sliding walls, as well as reduces lateral displacement by 35%. The collapse pattern that occurs is daktail with the formation of plastic joints starting from the beam before the column, in accordance with the concept of strong column-weak beam. This study concludes that the use of sliding walls in the multi-storey building of Panca Budi Development University significantly improves the seismic performance of the structure and meets safety requirements in accordance with SNI 1726:2019 concerning Earthquake Resistance Planning Procedures for Building and Non-Building Structures. This study recommends the implementation of sliding walls as an effective solution to improve seismic resistance in high-rise buildings in the middle earthquake zone.